Shut up and listen! hard business truths that will help you succeed - Tilman Fertitta ([New York] HarperCollins Leadership, 2019)
For aspiring entrepreneurs or people in business, this book will help you take your company to the next level. When you put this book down, youll know what youre doing right and what youre doing wrong to operate your business, and if youre just getting started, it will help set you up for success.
Keywords: Success in business